Impact of COVID on Professionals Addressing Psychosocial Needs of People With Diabetes: An International Survey - Wagner, Julie; Cummings, Caroline; Feinn, Richard; Kanc, Karin; Kos, Miha (Frontiers in Clinical Diabetes and Healthcare, 2022)
We investigated how COVID-19 has disrupted the work of health professionals who address behavioral and psychosocial needs of people with diabetes (PWD). English language emails were sent to members of five organizations that address psychosocial aspects of diabetes, inviting them to complete a one-time, anonymous, online survey. On a scale from 1=no problem, to 5=serious problem, respondents reported problems with the healthcare system, their workplaces, technology, and concerns about the PWD with whom they work. Respondents (n=123) were from 27 countries, primarily in Europe and North America. The typical respondent was a woman, aged 31-40 years, who worked in an urban hospital in medicine or psychology/psychotherapy. Most judged that the COVID lockdown in their region was moderate or severe. Over half felt moderate to serious levels of stress/burnout or mental health issues. Most participants reported moderate to severe problems due to the lack of clear public health guidelines, concerns with COVID safety of themselves, PWD, and staff, and a lack of access or knowledge on the part of PWD to use diabetes technology and telemedicine. In addition, most participants reported concerns with the psychosocial functioning of PWD during the pandemic. Overall, the pattern of findings reveals a high level of detrimental impact, some of which may be ameliorated with changes in policy and additional services for both health professionals and the PWD with whom they work. Concerns about PWD during the pandemic must go beyond their medical management and also consider the health professionals who provide them with behavioral and psychosocial support.